Proteome profile analysis reveals regulatory mechanisms in the liver of Carassius auratus under short‐term salinity stress (10‰, 48 h) - Rui Zhao; Muhan Meng; Xiaolian Liu; Shuang Hao; Xin Luo; Ning Wu; Lin Ma; Sun Hongqing; Hongzheng You (Journal of Fish Biology, 2026)
Carassius auratus , a commercially important species in the ornamental aquarium industry, is sensitive to salinity fluctuations. In this study, 30 C. auratus of length 13.1 ± 2.9 cm and weight 103.8 ± 40.8 g/fish were placed into six plastic tanks (80 L) with five fish per tank. About 15 fish were exposed to 10‰ salinity for 48 h, while another 15 fish were kept in freshwater and continuously aerated (0‰) as a control. To investigate the effects of short‐term salinity stress (10‰, 48 h), proteomic profiling of the liver was conducted. Short‐term salinity stress resulted in 104 upregulated and 95 downregulated proteins in the liver of C. auratus . Gene ontology enrichment analysis indicated significant enrichment in areas such as proteolysis, nitrogen compound transport, cellular component, peptidase activity, acting on L‐amino acid peptides, endopeptidase activity, serine‐type peptidase activity and enzyme inhibitor activity. Furthermore, the Kyoto Encyclopedia of Genes and Genomes enrichment analysis identified mitogen‐activated protein kinase kinase kinase 7 (MAP3K7) as an essential regulated protein in the IL‐17 signalling pathway and glutamine synthetase (GS) in the arginine biosynthesis pathway. These findings suggest that short‐term salinity stress induces significant proteomic changes in C. auratus , with functional enrichment in peptide metabolism and enzyme regulation. Notably, MAP3K7 and GS may play crucial roles in coping with short‐term salinity stress, providing new insights into the proteomic regulatory mechanisms of C. auratus under short‐term salinity stress.

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .